The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1519/jsc.0000000000001756
|View full text |Cite
|
Sign up to set email alerts
|

The Biomechanical Demands on the Hip During Progressive Stepping Tasks

Abstract: Hatfield, GL, Charlton, JM, Cochrane, CK, Hammond, CA, Napier, C, Takacs, J, Krowchuk, NM, and Hunt, MA. The biomechanical demands on the hip during progressive stepping tasks. J Strength Cond Res 31(12): 3444-3453, 2017-Functional hip strengthening exercises are important components of lower extremity (LE) rehabilitation and include single-leg squats (SLS), step-downs (SD), and step-ups (SU). The biomechanical demand of these tasks is unclear. This repeated-measures study determined hip biomechanical demands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…However, the differences in EMG activity that were found by these authors were lower in comparison to those of the present study, possibly because these authors used lower loads (the participants' body weights) as well as lower boxes (15.24 cm), compared to the present study. Most recently, Haltfield et al [48] also found greater activation in the VL and VM, followed by…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the differences in EMG activity that were found by these authors were lower in comparison to those of the present study, possibly because these authors used lower loads (the participants' body weights) as well as lower boxes (15.24 cm), compared to the present study. Most recently, Haltfield et al [48] also found greater activation in the VL and VM, followed by…”
Section: Discussionmentioning
confidence: 88%
“…We found no study that specifically used this load, since the literature features a great deal of heterogeneity regarding the loads that are used in the studies of sEMG. Most of the studies on unilateral exercises usually use the participant's own body weight because they are oriented toward rehabilitation purposes [22,48,51,55,57]. Deforest et al [31] used 85% 1 RM to analyze Double-leg squats and 50% of said load for Single-leg squats.…”
Section: Plos Onementioning
confidence: 99%
“…1,2 The overall normal movement patterns during descent in both the SLST and SDT include hip and knee flexion with anterior pelvic tilt, trunk flexion, and hip adduction with knee internal rotation and abduction. 1,3,4 Visual observation of the SLST and SDT has been shown to be reliable for evaluating kinematic and biomechanical deficiencies of the hip, pelvis, and trunk in healthy people. 5,6 These tests have also been established as valid for assessing dynamic lower extremity control and hip muscle function in both healthy people and those with diagnosed hip chondropathy.…”
mentioning
confidence: 99%
“…1 An increase in hip-abduction kinematics needed during the SDT can cause greater activation of the medial and lateral hamstrings as compared with the SLST. 4 Conditions associated with hip-joint pain in the absence of severe degenerative joint disease are defined as nonarthritic hip pain and include femoroacetabular impingement (FAI), acetabular labral tears, dysplasia, structural instability (ie, acetabular retroversion, femoral anteversion), and ligamentum teres tears. 11,12 These conditions are believed to result from repetitive microtrauma that occurs during dynamic movement between the proximal femur and the acetabulum.…”
mentioning
confidence: 99%
See 1 more Smart Citation